KARAKTERISTIK PASIEN TUBERKULOSIS PARU KASUS BARU YANG DINYATAKAN SEMBUH DI POLI PARU RSUD ARIFIN ACHMAD PERIODE JANUARI 2011-DESEMBER 2013 - Kiki Yuliana; Indra Yovi; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Pulmonary tuberculosis (TB) is a lung parenchyma infectious disease caused by Mycobacterium tuberculosis and transmission through droplet. New case of TB is a patient who has never had treatment for TB or who has taken anti-TB drugs for less than one month. Cured is patient who was completed treatment with sputum smear-negative in the last month of treatment and at least on one previous occasion. This research was a descriptive study using retrospective appoarchment, which was conducted in the TB-01 form and ward patients. Sample collected from 36 patients that included in inclusion criteria. The results showed that patients new case of pulmonary tuberculosis declared cured in lung department of arifin achmad hospital showed large proportion in the age group 35-44 and 45-54 years (respectively 22,2%), the most gender is male (55,6%), most level education is senior high school (58,3%), most work is entrepreneur (77,7%),most drugs swallowing control (PMO) is any PMO (86,1%), most regularity of taking medicine is regularly (61,1%), most regimen anti tuberculosis is KDT/FDC (94,4%), most sputum reexamination is disobedience (58,3%), and most BTA (basil tahan asam) inspection result is BTA (+) (100%).Key word :Tuberculosis (TB), new case, cured